A Qualitative Framework of Cumulative Risk and Protection for Understanding Neurodevelopment and Clinical Progress: A Multiple Case Study Approach. Issue 1 (2nd January 2021) - Bondi, Bianca C.; Pepler, Debra J.; Motz, Mary; Andrews, Naomi C.Z.
ABSTRACT: Prenatal substance exposure is a serious public health concern given that such exposure is associated with deficits across various neurodevelopmental domains. Mothercraft's Breaking the Cycle (BTC) is a child maltreatment prevention and early intervention program in Canada for pregnant and parenting women who use substances and their children (0–6 years). Case studies of three substance-exposed sibling groups that received services at BTC are described to depict the spectrum of clinical progress that can be observed. The purpose of this study was to use our clinically and theoretically grounded, cross-domain cumulative risk and protection framework, previously developed for quantitative analyses, to qualitatively describe cumulative risk and protection. Using this framework within a qualitative case study approach yields insights into how contexts of risk and protection contribute to clinical progress. This study offers direction for future research to enhance understanding of the spectrum of clinical progress in substance-exposed families accessing early intervention. We discuss the clinical utility of this qualitative framework for case formulation and treatment planning. Understanding the balance between contexts of risk and protection qualitatively, and the link with neurodevelopment and clinical progress, can inform evidence-based, multisystemic early interventions that target key risk factors and promote salient protective factors.